Respiratory Syncytial Virus in Otherwise Healthy Prematurely Born Infants: A Forgotten Majority - Paes, Bosco (American Journal of Perinatology, 2018)
Healthy, premature infants ≤35 weeks' gestational age (wGA) are universally recognized to be at an increased risk of perinatal morbidity and mortality. Serious respiratory syncytial virus (RSV) lower respiratory tract infection imposes an additional burden of illness on these infants following hospitalization. Incurred morbidities relative to term infants include longer lengths of hospital stay, admission to intensive care, and need for oxygen and mechanical ventilation, all of which are associated with increased hospital costs. The highest morbidities are experienced by premature infants who are youngest (<3 months' chronological age) and are of lower gestational age. Short- and long-term follow-up indicates that healthy preterm infants both of lower gestational age and who are late preterm have obstructive lung function at baseline, which is further compromised by RSV-related infection during infancy. There is increasing evidence that childhood exposure to an episode of RSV infection may set the stage for an abnormal respiratory function trajectory, which, in adulthood, leads to chronic obstructive pulmonary disease. Healthy premature infants <32 wGA merit RSV prophylaxis based on existing data, whereas moderate- and high-risk preterm infants 32 to 35 wGA should be selectively and cost-effectively targeted for prophylaxis using validated risk scoring tools and country-specific thresholds for funding.
Keywords: healthy premature infant; hospitalization; morbidity; palivizumab; prophylaxis; respiratory syncytial virus